Language Style Used by Tony Stark in the Avengers: Infinity War - Vivin Indah Sari S., Ida Ayu; Udayana, Nyoman; Parthama, I Gusti Ngurah (Udayana Journal of Social Sciences and Humanities; Vol 5 No 2 (2021): UJoSSH, September 2021DO - 10.24843/UJoSSH.2021.v05.i02.p03, 2021)
Language styles create many impressions in the spoken form and writing. Therefore, language style becomes a form of inner expression that is typical of a speaker of the language. A person usually chooses a word or sentence in such a way as to achieve a specific goal for the listener. This study aimed to discuss the language style and its function that used by Tony Stark in the Avengers: Infinity War movie. The discourse of Tony Stark in Avengers: Infinity War movie were taken as the data for this study. The data has collected by observing and taking note the conversation of Tony Stark and other characters. It was analyzed by the Sociolinguistic theory from Holmes (2004). Based on the data analysis, the result shows that Tony Stark used more standard language to communicate with his Avengers partners. It is because this movie had a genre of action-science fiction which made Tony Stark face more serious and formal situations. There were also found five functions of language styles used by Tony Stark, there are: expressive function, directive function, referential function, phatic function, and poetic function.